PERBEDAAN KEMATANGAN SEKOLAH ANTARA ANAK YANG MENGIKUTI DAN TIDAK MENGIKUTI LES BACA, TULIS, HITUNG (Penelitian pada Siswa TK Swasta di Jakarta) - Isabela Rosalina Ferly; Yapina Widyawati (Fakultas Psikologi Universitas Tarumanagara, 2016)
Some parents gave early reading, writing, and arithmetic course for their children from an early age. Some of the reasons were the earlier the better, child's cognitive ability is foremost, as well as the current demands of reading, writing, and arithmetic for entry to primary school. This study aimed to examine whether there are differences in school maturity between children who attend and not in that course. This research was conducted with non experimental and quantitative approach. 100 private kindergarten students, parents, and teachers were participating in this study. The result showed that there was not significant differences in school maturity. Most participants have matured in most subtests as well as in the category hesitate on fine motor subtests and critical observations. The percentage of children in the category of mature and in between, were almost equal in children who participate and not in that course.Keywords: school maturity, reading, writing, arithmetic